2003
DOI: 10.1111/j.1530-0277.2003.tb02713.x
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2 Receptor Binding, Drd2 Expression and the Number of Dopamine Neurons in the BXD Recombinant Inbred Series: Genetic Relationships to Alcohol and Other Drug Associated Phenotypes

Abstract: The range of difference in receptor binding for the RI strains was approximately 2-fold in all regions examined, the core, the shell of the nucleus accumbens (NAc) and the dorsomedial caudate-putamen (CPu); heritability in all regions was moderate--(h2 approximately 0.35). Drd2 expression in forebrain samples from the RI and parental strains ranged 1.5- to h2-fold and was moderate-0.47. Variation in the number of tyrosine hydroxylase (TH) positive neurons was moderate, 41% and 26% and h2 was low--0.19 and 0.15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…Genetic and molecular biological studies have recently linked the Nr-CAM (in both mouse and human populations) with susceptibility to and consequences of addiction (Ishiguro et al 2006;Minana et al 2000), aberrant drug-seeking behavior and dysfunctional brain-based drug reward systems (Hitzemann et al 2003). In support of these contentions, it has been observed that mice with reduced levels of Nr-CAM expression manifest less drug-conditioned place preference (Hall et al 2004;Lin et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic and molecular biological studies have recently linked the Nr-CAM (in both mouse and human populations) with susceptibility to and consequences of addiction (Ishiguro et al 2006;Minana et al 2000), aberrant drug-seeking behavior and dysfunctional brain-based drug reward systems (Hitzemann et al 2003). In support of these contentions, it has been observed that mice with reduced levels of Nr-CAM expression manifest less drug-conditioned place preference (Hall et al 2004;Lin et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine transmission has been found to modulate multiple facets of impulsivity as well as effort-based discounting (Cardinal et al, 2000;Robbins, 2002;Floresco et al, 2008b). We quantified D1 and D2 dopamine receptor gene expression because such measures, particularly in the prefrontal cortex and striatum, have been demonstrated to be predictive of some aspects of cognition as well as vulnerability to drugs of abuse (Thanos et al, 2001;Hitzemann et al, 2003;Belin et al, 2007;Briand et al, 2008;Loos et al, 2010;Kramer et al, 2011). We found that expression of both D1 and D2 receptor mRNA in specific brain regions was predictive of impulsive action.…”
Section: Data Summarymentioning
confidence: 97%
“…In this approach one can index nucleic acid polymorphisms throughout the genome and correlate those polymorphisms with behavioral or biological phenotypes. This approach has proven successful as a first step to identifying polygenes affecting, for example, hippocampal neurobiology (Lassalle et al, 1994), alcohol pharmacology (Rodriguez et al, 1994;Buck et al, 2002) and cocaine pharmacogenetics (Phillips et al, 1998;Jones et al, 1999), dopamine neurochemistry Hitzemann et al, 2003) immunology (Pereira et al, 1997;Hsu et al, 2002) haloperidol sensitivity (Kanes et al, 1996) and other phenotypes.…”
Section: Introductionmentioning
confidence: 99%